Heated tobacco product use prevalence and temporal trends among the German population: a series of representative cross-sectional household surveys, 2018–2023 - Sabrina Kastaun; Daniel Kotz; Stephanie Klosterhalfen; Alex Maximilian Keller (BMJ Open)
Objectives Heated tobacco products (HTPs) are electronic devices that heat tobacco instead of burning it to produce an inhalable aerosol. This study aimed to investigate usage patterns, sociodemographic and socioeconomic factors, as well as co-use characteristics of people who use HTPs within the German population to inform interventions and preventive measures.Methods We conducted analysis with pooled cross-sectional data from the German Study on Tobacco Use (DEBRA) from June 2018 till November 2023. We estimated weighted, descriptive and bimonthly data on current and ever HTP usage and descriptive data on user patterns. To analyse the variance between people who ever versus people who never used HTPs in relation to user characteristics, we performed χ² tests and calculated percentages and CIs.Results The proportions of both people who currently use and people who ever used HTPs have increased from 2018 (current user: 0.1% [95%CI: <0.01 to 0.35]; ever user: 1.9% [95%CI: 1.36 to 2.60]) to 2023 (current user: 1% [95%CI: 0.62 to 1.52]; ever user: 8.4% [95%CI: 7.25 to 9.65]). Compared with people who never used HTPs, people who ever used HTPs were more likely to be male, younger and living in urban regions. On average, people who currently use HTPs use 7.3 (SD=7.4) tobacco sticks per day. IQOS was the most used brand, and 56% used HTPs with aroma technologies. The main reason to use HTPs was ‘because they are less harmful than tobacco that is burned’.Conclusion HTP use has increased in Germany, particularly among younger males in urban areas. Public health interventions should target these demographics, focusing on raising awareness about potential health risks. The ban on aroma components in Germany may reduce the appeal for new users. Continuous monitoring is essential to assess the long-term impact of HTPs.